Przekłady literatury słoweńskiej w Polsce w latach 2007—2013 — komentarz - Gawlak, Monika (Przekłady Literatur Słowiańskich, 2014)
Slovenian literature translations published in Poland between 2007—2013 — the commentary The commentary constitues a presentation of Slovenian literature translations published in Poland between 2007—2013. In mentioned period of time the translation of prose (among others written by Jančar, Virk, Žabot, Mazzini, Vojnovic, Möderndorfer, Frančič, Novak) and Slovenian poetry (Šalamun, Čučnik, Kosovel, Frančič, Osojnik, Kušar) appeared both as independent book publications as well as texts presented in periodicals and regular press. Also publications printed as anthology and releases which were a result of translation workshops were developed. In the commentary the author’s concern focuses mainly on books publications due to the fact that they are shaping the literary awareness of secondary culture. It is comforting that presently the increasing tendency for publishing translations of Slovenian literature can be observed. There is a growing need to strengthen and complement the image of Slovenian culture in the Polish reader’s consciousness, a kind of “cultural stereotype” which the reading community assimilate along with the growth of another texts. From the perspective of reception the most important issue seems to be that translations of Slovenian authors (besides Jančar, Virk and Čučnik) were published by independent, local and niche publishing houses. It is clearly seen that creating a coherent cultural‑publishing strategy and providing appropriate popularizing strategy would contribute to enriching, creative dialogue between Slovenian and Polish literature. Key words: literary translation, Reception of Slovenian literature, cultural politics, translations in Poland.